Can resistant Helicobacter pylori infection be estimated histologically: Effects of gastric histology on eradication rates of Helicobacter pylori infection - Vildan TAŞKIN; Esin ÖZYILKAN; Abdullah AYDIN; Faruk ÇETİN and Erdal ESKİOĞLU and Tankut KÖSEOĞLU (Turkish Journal of Gastroenterology, 2019)
-